Socialization of Legal Understanding Towards Street Merchants (PKL) who Provide Trading in Locations that are Prohibited from A Progressive Law Enforcement Perspective - Yuha Farisa Zukhruf; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2023)
This research aims to provide a description of the distribution of inheritance in Dawung village and provide a description of the Islamic perspective on the practice of distribution of inheritance carried out by the local community. This research uses descriptive qualitative methods. The data sources used are primary data sources which come from interviews and secondary data sources, namely sources obtained based on the results of reviewing books, journals and other written works. The data in this research was collected using literature study and interviews and then analyzed qualitatively. The results of the research prove that the practice of dividing inheritance property in Dawung village uses a traditional inheritance law system using an equal distribution system in which inheritance property is divided equally between daughters and sons, namely 1: 1, even though the majority of people in Dawung village embrace Islam. This is done in order to maintain and guarantee the integrity and harmony of the community so that there are no disputes between family members. Islam considers the practice of dividing inheritance as a shohih al u'rf which often arises in special social life and this distribution is considered valid for a society that has a culture like this because the components of consent and justice according to a society are the result of an agreement between the heirs. as well as the surrounding environmental situation.